ФРАНЦУЗСКИЙ ЯЗЫК: МЕТОДИКА ПРЕПОДАВАНИЯ («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
Methodological materials are presented that allow organizing training in an additional educational program for teaching French from the 1st year as part of extracurricular activities. The content, forms of organization of training and forms of monitoring and summing up the results of mastering the program are characterized. Much attention is paid to characterizing the results of mastering the program, principles and conditions for its implementation.
Keywords: methods of teaching French, foreign language, additional program, unity of personal, meta-subject results.